THE MEANING OF THE WORD “DAN/ATAU” IN INDONESIAN LAWS AND REGULATIONS - Irnawati, Irnawati; Ardhianti, Mimas (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Improper meaning of